Microscopic Simulation & Microscopic Analytical Model Comparison in Analyzing a Signalized Intersection - Azlina, Ismail; Intan Suhana, Mohd Razelan; A., Zulkiple; Siti Fatimah, Che Osmi; Norhaiza, Ghazali; Aizat, Alias (Penerbit UMP, 2011)
Most of intersections are complex maneuvering areas with high number of traffic conflicts of crossing, merging and diverging. It is also suffered from the problem of flow and capacity that passing through the intersections since many factors have influenced the efficient of the intersections. Due to the complexity task in analysis of a signalized intersection, the used of microscopic simulation model has become very popular for traffic engineers and planners in dealing with such activities. This is because of great advantage that offers by this model especially on the ability to realistically model a complex transport system and it provides users with the most desirable statistics and performance measures of alternative design or existed transport system. This study aims to assess the consistency of the results generated by micro simulation models in analysis the performance of a signalized intersection. In this case, a micro analytical model will be used alongside micro simulation model. Therefore, the results produced by both models could be compared in order to assess for the consistency of micro simulation model. To carry out the modelling of micro simulation and micro analytical, CUBE Dynasim and aaSIDRA has been used as a tool accordingly. A four legged signalized intersection at South Road and Henley Beach Road in Adelaide was selected to serve as a case study. The result comparison was based on the performance measures of the signalized intersection such as the traffic flows, delay and level of service (LOS). In this study, the results demonstrated by CUBE Dynasim microscopic simulation model was reasonably consistent with aaSIDRA microscopic analytical model in analyzing a signalized intersection.